The Effects of Leadership Style and Work Motivation on Job Satisfaction among Employee - Andi Indriani Ibrahim; Fitri Sari Ningsih; Risnawati; Syahir Natsir (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2025)
Study aims to analyze the Influence of Leadership Style and Work Motivation on Job Satisfaction of Maraja Mart Supermarket Employees in Ampana. The sampling technique that will be used in this study is Saturated Sampling, with a sample size of 30 respondents. Data collection using interviews, observations and questionnaires that have been tested for validity and reliability. The analysis method uses Multiple Linear Regression. The results of the study indicate that Leadership Style and work motivation simultaneously have a significant effect on the job satisfaction of Maraja Mart Ampana supermarket employees. Leadership style partially has a significant effect on the job satisfaction of Marja Mart Ampana supermarket employees. Work motivation partially has a significant effect on the job satisfaction of Maraja Mart Ampana supermarket employees.